2007
DOI: 10.1037/0096-1523.33.6.1495
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from object substitution masking induced by transient suppression of visual motion processing: A repetitive transcranial magnetic stimulation study.

Abstract: Object substitution masking is a form of visual backward masking in which a briefly presented target is rendered invisible by a lingering mask that is too sparse to produce lower image-level interference. Recent studies suggested the importance of an updating process in a higher object-level representation, which should rely on the processing of visual motion, in this masking. Repetitive transcranial magnetic stimulation (rTMS) was used to investigate whether functional suppression of motion processing would s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 69 publications
3
16
0
Order By: Relevance
“…To the extent that featural similarity acts as an object-individuation cue, this is consistent with the object-updating account (Lleras & Moore, 2003). Moreover, it has been shown that rTMS applied to V5/MT+ reduces masking (Hirose et al, 2007). This dovetails with the object-updating account, since V5/MT+ processes motion (Born & Bradley, 2005), which inherently involves updating the location of an object over time.…”
Section: Object Updating and Object Substitutionsupporting
confidence: 61%
See 1 more Smart Citation
“…To the extent that featural similarity acts as an object-individuation cue, this is consistent with the object-updating account (Lleras & Moore, 2003). Moreover, it has been shown that rTMS applied to V5/MT+ reduces masking (Hirose et al, 2007). This dovetails with the object-updating account, since V5/MT+ processes motion (Born & Bradley, 2005), which inherently involves updating the location of an object over time.…”
Section: Object Updating and Object Substitutionsupporting
confidence: 61%
“…That said, it still does not provide a complete account for the full gamut of OSM findings. For example, there are many objectupdating effects in OSM (e.g., Hirose et al, 2007), which we will discuss in the next section, on which this model is silent. Similarly, in its current form, this model does not predict the nonmonotonicity that OSM functions can produce Goodhew, Dux, Lipp, & Visser, 2012;Goodhew, Visser, Lipp, & Dux, 2011a): That is, with prolonged mask exposure (e.g., 640 ms), there can be an improvement in target identification accuracy, relative to intermediate mask durations (e.g., 240 ms), yielding a Ushaped function of masking across mask exposure (Goodhew et al, 2012;Goodhew et al, 2011a).…”
Section: Theories Of Osmmentioning
confidence: 99%
“…The conscious perception of a stimulus in these accounts is the result of the system reaching a stable state of resonance between the feedforward and reentrant signals. Recent evidence in support of this view comes from electrophysiological data from monkey (Fahrenfort et al, 2007) and from transcranial magnetic stimulation in humans (Ro et al, 2003; Hirose et al, 2005, 2007). For instance, Hirose et al (2005, 2007) applied brief high-intensity magnetic pulses to the brain region MT/MT+ in human participants and reported that it disrupted masking and led to increased visibility of a target that would otherwise have been invisible.…”
Section: Discussionmentioning
confidence: 97%
“…Recent evidence in support of this view comes from electrophysiological data from monkey (Fahrenfort et al, 2007) and from transcranial magnetic stimulation in humans (Ro et al, 2003; Hirose et al, 2005, 2007). For instance, Hirose et al (2005, 2007) applied brief high-intensity magnetic pulses to the brain region MT/MT+ in human participants and reported that it disrupted masking and led to increased visibility of a target that would otherwise have been invisible. Notably for the present study, reentrant neural activity projecting from the MT cortex is also involved in motion perception, and thus may be the neural mechanism by which perception of a target in motion is influenced by signals generated by the contextual shapes surrounding a target shape (Liu et al, 2004; Muckli et al, 2005; Sterzer et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…This makes it hard for observers to report the old appearance of the object when object-updating occurs, as demonstrated in studies on object-substitution masking [12][15], backward masking [16], and visible persistence along a motion trajectory [17]. A previous study [15] suggested that the plastic deformation in apparent motion as described above is related to object updating, and a close relationship between object-updating and visual motion has been confirmed in a transcranial magnetic stimulation study [18].…”
Section: Introductionmentioning
confidence: 98%